Comparison of EDTA and Boric Acid Irrigation in Terms of Root Canal Dentin Microhardness and Sealer Penetration Depth - İnce Yusufoğlu, Selen; Saricam, Esma; Bulak, Neslihan; Güngörmüs, Mustafa; Tulumbacı, Fatih; Özcan, Suat (UI Scholars Hub, 2023)
Chemo mechanical preparation is one of the important stages for successful endodontic treatment, and Boric acid has been proposed as an alternative irrigation solution for root canal treatment. Objective: The purpose of this study was to evaluate the effect of irrigation with boric acid (BA) and EDTA on the mineral content and microhardness of dentin and penetration of the AH Plus root canal sealer. Methods: 63 single-rooted teeth were instrumented. Microhardness analysis, 45 teeth were cut longitudinally and then transversely to obtain dentin. Pre- and post-treatment microhardness values were measured. The samples were randomly assigned into 3 groups (n = 15) for irrigation solution: distilled water, 17% EDTA, and 5% BA. The 18 roots were irrigated with three solutions (n = 6). Nine of the roots were filled with AH-Plus for confocal laser scanning microscopy analysis, and the others were used for XRD analysis. Results: The results were evaluated with the ANOVA test. BA caused a significant decrease in microhardness value in apical and coronal parts (p < 0.05), while EDTA reduced only in coronal parts (p < 0.05). Conclusion: BA provided higher sealer penetration ability. BA reduced the microhardness and provided better sealer penetration.